Pengenalan Sistem Mesin Pesawat Bagi Siswa SMK Nasional Berbah - Ahmad Mamba’udin; Elfrida Rizky Riadini; Arif Pambekti (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This activity aims to provide students of SMK Nasional Berbah with basic insights and understanding of aircraft engines. The limited access to practical knowledge of aviation technology serves as the main rationale for implementing this program. Through this activity, students receive materials covering fundamental theories of aircraft engines, types of engines, the working principles of turbine and piston engines, as well as visual and interactive demonstration sessions. The methods used include interactive lectures, group discussions, and component introductions through video-based media. The results indicate an improvement in students' understanding of basic aircraft engine concepts and a growing interest in the field of aviation. This activity aims to spark vocational school students’ interest in aviation science.